Beauvais Cathedral: The Ambition, Collapse and Legacy of Gothic Engineering - Rubén Rodríguez Elizalde (Heritage)
The Cathedral of Beauvais remains one of the most enigmatic and ambitious architectural undertakings of the Gothic era. Conceived to surpass all other cathedrals in height and grandeur, it achieved unprecedented verticality but collapsed under the weight of its own aspirations. This article reexamines Beauvais as a case study in Gothic engineering—its structural daring, tragic failures, and enduring legacy—through a multidisciplinary approach combining historical research, technical analysis, and philosophical interpretation. Structured in accordance with standard academic conventions, the article outlines its methodology, presents a detailed reconstruction of the cathedral’s history, and discusses its broader cultural and conservation implications. A dedicated discussion section explores not only the engineering and symbolic significance of Beauvais but also the limitations of the present study and potential avenues for future research. Ultimately, the cathedral is framed not merely as a failed monument, but as a lasting testament to the human drive to build beyond known limits.